Kit for diagnosis of BK virus infection by the real-time Polymerase Chain Reaction method (PCR) - K. L. Dziadziulia; T. V. Amvrosieva; N. V. Paklonskaya; Z. F. Bogush; V. A. Zemlianski; S. K. Loziuk (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The presented work comprises information about developed by Republic Scientific and Practical Center for Epidemiology and Microbiology the diagnostic kit for detection the BK virus DNA in clinical samples by the real-time Polymerase Chain Reaction method. Accomplished studies showed high level its diagnostic sensitivity and specificity. Suitability of developed kit for laboratory BK virus diagnosis was demonstrated.